A Comparison of Single-Particle and Particle-Bed Breakage of Mineral Ores under Compressive Loading - D. Gong; C. Sun; T. Sun; J. Kou (International Mineral Processing Congress, 2018)
"HPGRs (high pressure grinding rollers) have demonstrated higher energy efficiency than conventional comminution equipment due to their application of particle-bed breakage mechanism. In the past decades, a large number of studies have been conducted to understand the characteristics of particle-bed breakage, however, few of them concerned the difference between single-particle and particle-bed breakage in compression comminution. This comparison is able to demonstrate possible advantages of particle-bed against single-particle in a breakage event due to the isolation of the effect of force loading mechanism. The present study investigated progeny fragment size and energy efficiency of these two breakage methods at variable energy inputs and particle sizes. The results show that at low energy inputs of around 0.25 kWh/t, the numbers of fines resulting from the two breakage methods are very similar. However, at higher energy inputs of around 1.0 or 2.0 kWh/t, particle-bed breakage generated significantly more fines. From the perspective of newly generated surface energy, particle-bed breakage is obviously more energy efficient than single-particle breakage at energy inputs between 1.0 and 2.0 kWh/t. It was also found that HPGRs demonstrate high energy utilization rate in generating new surface energy within their typical range of specific energy input. INTRODUCTION Rock comminution is an important and energy-intensive process in mining operations. Nowadays, decreasing head grade and mineral liberation size of ore deposits greatly increase the energy cost of comminution process. HPGRs have been successfully applied in the mining industry to improve the energy performance of comminution circuits. Typically, 10 to 30% of energy saving can be achieved due to the application of HPGR (Wang et al., 2013; Casteel, 2005; Günter et al., 1996)."